2002
DOI: 10.1002/1527-2648(20020717)4:7<490::aid-adem490>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Mullite Whiskers Derived from an Oxide Mixture Activated by a Mechanochemical Process

Abstract: With increasing mixture ratio the homogeneity of the samples is worse: the distribution of capillary sizes is greater and the number of capillaries decreases. Al 2 O 3 samples were produced up to a mixture ratio of 10:1After sintering the samples have rough surfaces (Fig. 7), but we achieved a smooth surface by mechanical grinding. Grinding samples with high porosity is difficult; the samples must be infiltrated first.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The energy applied to the powder, reduces the grain/particle sizes in the first place. Besides, in some cases, chemical reactions may also take place during milling and in some others, the reaction temperature may even be lowered, depending on the amount of energy stored in the particles [18,19]. Figures 3 and 4 show the XRD patterns of TAP and non-TAP melted powder.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…The energy applied to the powder, reduces the grain/particle sizes in the first place. Besides, in some cases, chemical reactions may also take place during milling and in some others, the reaction temperature may even be lowered, depending on the amount of energy stored in the particles [18,19]. Figures 3 and 4 show the XRD patterns of TAP and non-TAP melted powder.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…[6][7][8] Microsized mullite whiskers, as a good reinforcement material in ceramic-matrix composite, have been fabricated and extensively investigated. [9][10][11][12][13][14][15] Recent studies have shown that nanoscale whiskers such as nanowires or nanorods have better mechanical properties than their microscale counterparts. [16][17][18] Thus, mullite nanowires or nanorods are good composite reinforcements that could find important applications in functional ceramics due to their high * Authors to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a mixture of solids, a mixture of sols, or a mixture of sol and salts can each be used as the starting materials. Similarly, a variety of mullite preparation methods has been developed such as reaction sintering of mechanically mixed powders [7][8][9][10][11], hydrothermal treatment of mixtures of sols [12][13][14] and chemical vapour deposition [15][16][17][18]. On the other hand, different routes have been used for manufacturing of zirconia-mullite composites from mullite-zirconia or alumina-zircon mixture such as plasma spray using plasma arc [19][20][21], reaction sintering at elevated temperatures [22][23][24][25][26], crystallization of rapidly quenched melts of ZrO 2 -Al 2 O 3 -SiO 2 [27] and liquid infiltration technique [28].…”
Section: Introductionmentioning
confidence: 99%